International Perspectives on Joint Hypermobility: A Synthesis of Current Science to Guide Clinical and Research Directions. Issue 6 (3rd September 2022) - Nicholson, Leslie L.; Simmonds, Jane; Pacey, Verity; De Wandele, Inge; Rombaut, Lies; Williams, Cylie M.; Chan, Cliffton
Abstract: There is exponential clinical and research interest in joint hypermobility due to recognition of the complexity of identification, assessment, and its appropriate referral pathways, ultimately impacting management. This state-of-the-science review provides an international, multidisciplinary perspective on the presentation, etiology, and assessment of joint hypermobility, as it presents in those with and without a systemic condition. We synthesize the literature, propose standardizing the use of terminology and outcome measures, and suggest potential management directions. The major topics covered are (i) historical perspectives; (ii) current definitions of hypermobility, laxity, and instability; (iii) inheritance and acquisition of hypermobility; (iv) traditional and novel assessments; (v) strengths and limitations of current assessment tools; (vi) age, sex, and racial considerations; (vii) phenotypic presentations; (viii) generalized hypermobility spectrum disorder and hypermobility Ehlers-Danlos syndrome; and (ix) clinical implications and research directions. A thorough understanding of these topics will equip the reader seeking to manage individuals presenting with joint hypermobility, while mindful of its etiology. Management of generalized joint hypermobility in the context of a complex, multisystem condition will differ from that of acquired hypermobility commonly seen in performing artists, specific athletic populations, posttrauma, and so on. In addition, people with symptomatic hypermobility present predominantly with musculoskeletal symptoms and sometimes systemic symptoms including fatigue, orthostatic intolerance, and gastrointestinal or genitourinary issues. Some also display skeletal deformities, tissue and skin fragility, and structural vascular or cardiac differences, and these warrant further medical follow-up. This comprehensive review on the full spectrum of joint hypermobility will assist clinicians, coaches/sports trainers, educators, and/or researchers in this area.